Islamic law of trade and finance: a selection of issues - Billah, Mohd. Ma'sum (Ilmiah Publishers, 2003)
Development in trade and commercial activities under Shari'ah principles without parallel development of laws can result in destructive experience. Therefore, an attempt has been made in this research to come up with a piece of work on Islamic Law affecting some selected issues of contemporary trade and financial practices.